FACTORS INFLUENCING THE WORK EFFECTIVENESS OF FUNCTIONAL EQUIVALENCY OFFICIALS ON THE IMPLEMENTATION OF BUREAUCRATIC SIMPLIFICATION POLICY THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE IN BINTAN REGENCY - Ngaliman; Mohamad Gita Indrawan; Desi Efna (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study analyzes the factors that influence Effectiveness of the Work of Functional Equivalency Officials in the Implementation of the Bureaucratic Simplification Policy in the Bintan Regency Government, with job satisfaction as an intervening variable. The legal basis for bureaucratic simplification is regulated in PERMENPANRB NO. 25 OF 2021 concerning the Simplification of Organizational Structures in Government Agencies for Bureaucratic Simplification. The negative impact of this policy that needs to be anticipated is the psychological impact on Administrators (echelon III) and Supervisors (echelon IV) who will lose their positions. Using primary data from 153Functional Officials, this study found that Compensation and Organizational Commitment have a significant direct effect on Work Effectiveness, on the other hand Job Placement is proven to have an insignificant effect on Work Effectiveness, in addition Compensation, Job Placement and Organizational Commitment have a significant effect on Job Satisfaction. Job Satisfaction has a significant effect on Work Effectiveness. In the indirect effect, Compensation and Organizational Commitment have a significant effect on Work Effectiveness through Job Satisfaction. However, Job Placement does not have a significant effect on Work Effectiveness through Job Satisfaction. The proposed recommendation is to focus on increasing work effectiveness and other aspects that have a more direct effect on the psychological impact of Administrator (echelon III) and Supervisor (echelon IV) officials who will lose their positions.